A structural Model of Self-efficacy in Handball Referees - Diotaiuti, Pierluigi; Falese, Lavinia; Mancone, Stefania; Purromuto, Francesco (Frontiers in Psychology, 2017)
The study aimed to identify factors predicting self-efficacy in a sample of 248 Italian handball referees. The main hypothesis was that perception of teamwork efficacy would be a significant predictor of self-efficacy in handball referees. Participants completed an online questionnaire including Referee Self-Efficacy Scale (REFS) (α=0.85), Self-Determination Scale (SDT) (α=0.78), and an adaptation for Referees of the Sport Commitment Model (SCM) (α=0.80). Two hierarchical regression analyses have identified: 1) Enjoyment (ß=.226), Couple Efficacy (ß=.233), and Personal Awareness (ß=.243), as predictors of Self-Efficacy; 2) Span of Co-Refereeing (ß=.253), Perceived Quality of the Relationship (ß=.239), and Mutual Agreement (ß=.274), as predictors of Couple Self-Efficacy. A further SEM analysis confirmed the fit of a structural model of Self-efficacy considering the reciprocal influence of Couple Efficacy, Enjoyment and Awareness (χ 2: 5.67; RMSEA: .000; SRMR: .019). The study underlines the importance of teamwork (or co-refereeing) as it relates to enjoyment and awareness in officiating and how it enhances the psychological well-being of handball referees. Future studies should investigate the relationship between factors influencing perceived teamwork efficacy and officiating performance outcome.